Design and validation of a miniaturized SEA transmission system. (February 2018) - Baldoni, Andrea; Cempini, Marco; Cortese, Mario; Crea, Simona; Carrozza, Maria Chiara; Vitiello, Nicola
Abstract: Background: Enabling position/torque control with Series Elastic Actuators (SEAs) is a common trend in modern robotic research. Particularly, in the field of wearable robotics for assistance and rehabilitation, SEAs enable simultaneously torque control rendering a desired impedance, and an intrinsically safe compliance in the user-machine physical interaction. Hence they are usually preferred when deciding over an actuator architecture. However, their implementation is very hard to accomplish, due to the encumbrance, stiffness and torque requirements that these devices should meet. This is a particularly relevant problem for hand exoskeletons. Objectives: This paper presents a novel miniaturized SEA transmission system that can be easily integrated into a hand exoskeleton. The requirements for the elastic element were (i) limited encumbrance (maximum diameter of 18 mm, maximum length of 40 mm), (ii) low stiffness (around 1.6 N m/rad) and (iii) torque up to 0.3 N m. Methods: Two design solutions of miniaturized SEA transmission systems are presented (i.e. a cam-based and a tangential-spring design) along with their experimental validation. Both concepts have been manufactured and tested. The encumbrance, stiffness and maximum torque of the two elements have been quantified. The solution that matched the design specifications has been characterized in position and torque control. Results: The proposed design achieved a resulting equivalent stiffness of 1.985 N m/rad, maximum torque of 0.2 N m, low encumbrance (diameter: 11 mm; length: 37 mm) and parasitic stiffness equal to 0.5 N m/rad with 1.25 Hz movement frequency when controlled in zero-torque modality. Limitations: The miniaturized SEA element should be integrated into a hand exoskeleton to verify its performance in the final application. Conclusions: We present two mechatronic designs of a single-axis torque-sensitive miniaturized compliant element, and their experimental characterizations. One design solution resulted more suitable for being integrated into a hand exoskeleton.